Improve security monitoring knowledge management in IoT applications based on user behavior analysis - Hossein Amoozad-Khalili (مدیریت مهندسی و رایانش نرم)
Content retrieval and knowledge management services In IoT applications, user-aware applications always contain different information and require a lot of resources to meet user demand, and this requires a high cost to implement content retrieval and management monitoring services. Is knowledge. This article presents a way to monitor knowledge management as well as to store and retrieve user information in the Internet of Things. Using the proposed method, users can transfer their data to IoT storage servers with more security than similar methods without knowing how and where to store it. The purpose of this article is to create a user-centric system for security monitoring of knowledge management in IoT applications that can be easily used. In this regard, reducing the cost of resource allocation and knowledge management by intelligently reducing the amount of data received and the use of appropriate factors to increase the quality of IoT applications have been addressed.